2013
DOI: 10.1073/pnas.1300959110
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A delays the perinatal chloride shift in cortical neurons by epigenetic effects on the Kcc2 promoter

Abstract: Bisphenol A (BPA) is a ubiquitous compound that is emerging as a possible toxicant during embryonic development. BPA has been shown to epigenetically affect the developing nervous system, but the molecular mechanisms are not clear. Here we demonstrate that BPA exposure in culture led to delay in the perinatal chloride shift caused by significant decrease in potassium chloride cotransporter 2 (Kcc2) mRNA expression in developing rat, mouse, and human cortical neurons. Neuronal chloride increased correspondingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 40 publications
2
54
0
4
Order By: Relevance
“…Yeo et al (2013) studied the effect of bisphenol A (BPA), an additive commonly used during plastics manufacturing, on perinatal KCC2 regulation and found that BPA inhibits KCC2 upregulation and raises [Cl − ] i in neurons through an epigenetic mechanism. In addition to this GABA switch, KCC2 upregulation and subsequent [Cl − ] i downregulation signal interneuron precursors to halt migration during development (Bortone and Polleux 2009).…”
Section: − ] I During Neuronal Developmentmentioning
confidence: 99%
“…Yeo et al (2013) studied the effect of bisphenol A (BPA), an additive commonly used during plastics manufacturing, on perinatal KCC2 regulation and found that BPA inhibits KCC2 upregulation and raises [Cl − ] i in neurons through an epigenetic mechanism. In addition to this GABA switch, KCC2 upregulation and subsequent [Cl − ] i downregulation signal interneuron precursors to halt migration during development (Bortone and Polleux 2009).…”
Section: − ] I During Neuronal Developmentmentioning
confidence: 99%
“…By acting as a low-affinity ER agonists, BPA regulates the expression of synthetic enzymes of estrogen in neurons and thus the production of endogenous estrogen [16], affects the nuclear translocation of ER [17], and alters the genetic and epigenetic programming [18,19]. Consequently, EBE causes a wide range of effects on the mature neurons and their precursor cells: it alters the expression of development-related genes [18], shifts the ionic balance between the internal and external environment [20], and causes the hypotrophy of dendritic spines [21].…”
Section: Introductionmentioning
confidence: 99%
“…Yeo ve ark.nın yaptığı bir çalışmada, BPA'nın gelişmekte olan kortikal nöronlarda Kcc2 mRNA ekspresyonunu önemli ölçüde azalttığı gö-rülmüştür. 64 Nöroendokrin PC12 hücre hattı, hücre kültü-ründe sinir büyüme faktörü ile muamele edildiğinde; nöronal yapı kazanıp, dopamin başta olmak üzere nörotransmitterler salgılamaktadır ve dopaminerjik aktivite tayini için oldukça kullanışlıdır. Chen ve ark., MEHP [mono(zetilhekzil)ftalat] maruziyetinin PC12 hücrelerinin çoğalması ve gelişimi üzerindeki etkilerini incelemişlerdir.…”
Section: Hücre Kültürü çAlişmalariunclassified